Utilization of Canva Application as a Learning Media Video Creation - Rifki Zaitul Ikhlas; Rusdee Japakiya; Tika Muzayanah (Journal of Social Science Utilizing Technology, 2023)
Background. Thematic learning at Al-Bina 01 Koto Baru IT Elementary School during the co-19 pandemic has decreased in terms of quality and in the learning process. After research, this happened because of the lack of effectiveness of the learning process and the teacher's lack of optimization in conveying information related to learning material. Purpose. The purpose of this research is to create lesson media for students so that lessons become more interesting and students are more enthusiastic in learning. Method. This article The method used in this research is a qualitative method, because qualitative methods are very flexible and accurate. The model used in this test is the Design and Development (DnD) model. Results. The result of this study is that the canva application is very feasible and good to use as a learning media because, it can make lessons more interesting and fun. Conclusion. The conclusion of this study is that Canva application-based learning media is fully feasible to use in learning. Its utilisation is very interesting, in a learning situation in the midst of the current corona virus pandemic, the media created is very appropriate and makes it easier for teachers and students to complete the learning system.